A comparative overview on good fats and bad fats: guide to control healthy body - Banik, Sujan; Hossain, Mohammad (International Journal of Health, 2014)
An ideal food has six components such as carbohydrate, protein, fat, vitamin, salt and water. Every component is essential for our body for maintaining good health. Fat is necessary because it plays many critical roles in the body. It’s a very rich source of energy that supports in cell function, helps insulate the body, protects us from injury, helps vitamin absorption and adds flavor and texture to foods. As well as fat also responsible for the risk of developing obesity, diabetes and heart disease in many cases.  There are two classes of fat categorized in our listed daily food items; one is good fat (unsaturated fat) reduce the risk of developing heart diseases by helping to reduce blood cholesterol another is bad fat (saturated fat) can rise blood cholesterol. A fat diet, low in unsaturated fatty acids and rich in saturated fatty acids is thought to be an imperative basis of atherosclerosis and cardiovascular diseases. For maintaining good health, every person should update his knowledge regarding his food habits. This review focuses on the studies to summarize the good fats and bad fats from our daily listed food intake. Keywords: Fat, Cholesterol, Saturated Fat, Trans Fat, Unsaturated Fat, Good Fat, Bad Fat.